Pain sensitivity and injury associated with three methods of disbudding goat kids: Cautery, cryosurgical and caustic paste. (September 2018) - Hempstead, M.N.; Waas, J.R.; Stewart, M.; Zobel, G.; Cave, V.M.; Julian, A.F.; Sutherland, M.A.
Highlights: Cryosurgery (liquid nitrogen) or caustic paste debudding were evaluated in goat kids as alternatives to cautery disbudding. Cryosurgery and caustic paste debudding elevated pain sensitivity relative to cautery disbudding. Cautery disbudding caused skull injury, whereas the alternative methods did not. Average daily gains were not affected by disbudding method. Abstract: Pain sensitivity and skull/brain injury associated with cautery, cryosurgical and caustic paste disbudding were evaluated in goat kids. Kids (reared for meat; n = 280) were randomly assigned to one of four treatments ( n = 70 per treatment): (1) sham-handling (SHAM) or (2) cautery (CAUT), (3) cryosurgical (CRYO) or (4) caustic paste (CASP) disbudding. A pain sensitivity test was carried out 15 min pre-treatment and 1 h post-treatment. Skull/brain injury was assessed at post-mortem examination. Kids with evidence of injury to the skull/brain, as well as a random sample of kids ( n = 15 per treatment) without evidence of skull/brain injury, were selected for histological examination of brain tissue. Average daily gains (ADG) were calculated from body weight measurements taken 10 min pre-treatment and then at 2, 7 and 14 days post-treatment as a measure of the potential effects of pain or injury on growth. CASP and CRYO kids displayed higher pain sensitivity post-treatment than CAUT or SHAM kids, suggesting that they experienced more acute pain 1 h post-treatment. One of 70 CAUT kids had a perforated skull, but there was no histological evidence of brain injury in this animal; a further nine CAUT kids exhibited hyperaemia of the skull. The other treatments did not result in injury to the skull/brain. There was no evidence of a difference in ADG across treatments. Caustic paste and cryosurgical disbudding resulted in greater acute pain sensitivity than cautery disbudding; however, cautery disbudding has the potential to cause skull injury if performed incorrectly.